A randomized controlled trial of low-dose aspirin for the prevention of preeclampsia in women at high risk in China - Lin, Li; Huai, Jing; Li, Boya; Zhu, Yuchun; Juan, Juan; Zhang, Meihua; Cui, Shihong; Zhao, Xianlan; Ma, Yuyan; Zhao, Yangyu; Mi, Yang; Ding, Hongjuan; et al. (American journal of obstetrics and gynecology, 2022)
Low-dose aspirin has been the most widely studied preventive drug for preeclampsia. However, guidelines differ considerably from country to country regarding the prophylactic use of aspirin for preeclampsia. There is limited evidence from large trials to determine the effect of 100 mg of aspirin for preeclampsia screening in women with high-risk pregnancies, based on maternal risk factors, and to guide the use of low-dose aspirin in preeclampsia prevention in China. The Low-Dose Aspirin in the Prevention of Preeclampsia in China study was designed to evaluate the effect of 100 mg of aspirin in preventing preeclampsia among high-risk pregnant women screened with maternal risk factors in China, where preeclampsia is highly prevalent, and the status of low-dose aspirin supply is commonly suboptimal. We conducted a multicenter randomized controlled trial at 13 tertiary hospitals from 11 provinces in China between 2016 and 2019. We assumed that the relative reduction in the incidence of preeclampsia was at least 20%, from 20% in the control group to 16% in the aspirin group. Therefore, the targeted recruitment number was 1000 participants. Women were randomly assigned to the aspirin or control group in a 1:1 allocation ratio. Statistical analyses were performed according to an intention-to-treat basis. The primary outcome was the incidence of preeclampsia, diagnosed along with a systolic blood pressure of ≥140 mm Hg or a diastolic blood pressure of ≥90 mm Hg after 20 weeks of gestation, with a previously normal blood pressure (systolic blood pressure of <140 mm Hg and diastolic blood pressure of <90 mm Hg), and complicated by proteinuria. The secondary outcomes included maternal and neonatal outcomes. Logistic regression analysis was used to determine the significance of difference of preeclampsia incidence between the groups for both the primary and secondary outcomes. Interaction analysis was also performed. A total of 1000 eligible women were recruited between December 2016 and March 2019, of which the final 898 patients were analyzed (464 participants in the aspirin group, 434 participants in the control group) on an intention-to-treat basis. No significant difference was found in preeclampsia incidence between the aspirin group (16.8% [78/464]) and the control group (17.1% [74/434]; relative risk, 0.986; 95% confidence interval, 0.738–1.317; P=.924). Likewise, adverse maternal and neonatal outcomes did not differ significantly between the 2 groups. Meanwhile, the incidence of postpartum hemorrhage between the 2 groups was similar (6.5% [30/464] in the aspirin group and 5.3% [23/434] in the control group; relative risk, 1.220; 95% confidence interval, 0.720–2.066; P=.459). We did not find any significant differences in preeclampsia incidence between the 2 groups in the subgroup analysis of the different risk factors. A dosage of 100 mg of aspirin per day, initiated from 12 to 20 gestational weeks until 34 weeks of gestation, did not reduce the incidence of preeclampsia in pregnant women with high-risk factors in China.